IMPLEMENTASI PENGGUNAAN BAHASA INGGRIS PADA PEMBELAJARAN PAI DINIYAH ULYA KELAS 4 DENGAN METODE COLLABORATIVE LEARNING DI PONDOK PESANTREN MIFTAHUL HUDA AL-AZHAR CITANGKOLO - Kusmayadi, Yudi (Prodi PAI IAILM Suryalaya, 2018)
This research has a background that the era of globalizationraises the community's need for international schools that have theconcepts and systems needed for international standard schools thatactually implement the international system. Not only limited to thecover or international appearance, but the content and purposeaccording to the label displayed. So that it can answer people's anxiety.This study aims to describe the implementation of the use of English inPAI learning in diniyah ulya grade 4 by using the CollaborativeLearning method at Miftahul Huda Al-Azhar Islamic Boarding Schoolin Citangkolo Banjar, Including the preparation, implementation, and evaluation ofPAI learning, advantages and disadvantages, obstacles and solutionsfor Implementation of English using English in PAI learning in diniyahulya grade 4 by using Collaborative Learning method in Islamicboarding school Miftahul Huda al Azhar Citangkolo Banjar City Theresults of this study are (1) Implementation of the use of English in PAIlearning in grade 4th grade ulya Madrasah Ali Miftahul Huda Al AzharCitangkolo Banjar as a whole is in accordance with the guidelines oflearning programs with the use of foreign languages. language. (2) thebenefits of implementing the use of English motivate teachers andstudents to master English better, foster greater self-confidence inteachers and students, students avoid speaking improperly / disrespectfully, increasing students' abilities or skills (abilities) inEnglish, add teacher insight. Deficiencies in the form of timeeffectiveness (3) constraints in the form of teacher recruitment,standardization of the English language ability of PAI teachers,building madrasa culture, mastering English that is owned by teachersand students. Solutions in the form of conducting English learning forteachers and students, supplementary learning for students in theafternoon, conducting training for teachers, delegating PAI teachers tobuild madrasa culture, making corrections to lesson plans, andteaching practices (Micro Teaching), controlling language